Educational psychology cases for teacher decision-making - Greenwood, Gordon E.; Fillmer, H. Thompson (Upper Saddle River, N.J. : Merrill, 1999)
Case material is presented mainly in dialogue format, and cases are left open-ended in order to provoke discussion, analysis, and decision making. Each case begins with a listing of psychological theories and sets of principles for analyzing and resolving the case, provides other relevant material.
Includes bibliographical references.
Keywords: Educational psychology -- Case studies; Teaching -- Decision making; Teachers -- Training .